posted by Jorge .
Solve the following system using substitution. Write the solution as an ordered pair, (a, b).
b = a – 4
2a – 3b = -2
okay just equation 1 has b= a - 4 we can plug in a- 4 for b in equation 2 to give you;
2a - 3(a - 4) = -2
2a - 3a +4= -2
-a + 4 = -2
-a = -6
divide by negative 1 to make a postive
a= 6 now you can plug in 6 into either equation to solve for b
but i would use equation 1 since its so short b = 6- 4 , b= 2
i hope that helps if your confuse about anything with the above solution just ask and ill try to clarify
The only problem is, a=6 b=2 does not satisfy the original equations.
If you work it more carefully, you will wind up with
hint: -3(a-4) is not -3a+4